Regulation of insulin-like growth factor I gene expression in the human macrophage-like cell line U937. - Nagaoka, I (1990)
Activated macrophages release tissue forms of insulin-like growth factor I (IGF-I), 20-25-kD products of the IGF-I gene, thus providing an extracellular growth and differentiation signal at sites of inflammation. To examine the control of IGF-I gene expression in mononuclear phagocytes, the human macrophage-like cell line U937 was evaluated at rest and after surface activation with phorbol myristate acetate (PMA) or Ca2+ ionophore. Northern analysis and RNAse protection analysis with 32P-labeled IGF-I-specific probes demonstrated that the IGF-I mRNA transcripts of resting U937 cells were similar in size and amount to those of resting human alveolar macrophages, mononuclear phagocytes known to express the IGF-I gene. Nuclear run-off assays demonstrated that surface activation of U937 cells increased the transcription rate of the IGF-I gene four- to fivefold, a process that was inhibited by cycloheximide, suggesting that active protein synthesis was involved in the activation pathway. Despite this, cytoplasmic IGF-I mRNA levels after surface activation declined markedly, a process blocked by a protein kinase C inhibitor (for PMA activation) or a calmodulin antagonist (for Ca2+ ionophore activation). Like the increased transcription of the IGF-I gene, modulation of IGF-I mRNA transcript levels required active protein synthesis; in the presence of cycloheximide constitutive IGF-I mRNA levels increased and surface activation no longer caused a decrease in transcript number. Interestingly, surface activation caused a rapid release of IGF-I, even in the presence of a protein synthesis inhibitor, suggesting that mononuclear phagocytes have a preformed, stored, releasable pool of IGF-I. Together these observations demonstrate that IGF-I gene expression is complex and probably involves control of transcription rate, cytoplasmic mRNA levels possibly mediated through protein kinase C, calcium influx and calmodulin, and finally, release of preformed IGF-I from a storage pool.